1982
DOI: 10.1002/tera.1420250316
|View full text |Cite
|
Sign up to set email alerts
|

Malformations in infants of diabetic mothers

Abstract: Maternal insulin-dependent diabetes has long been associated with congenital malformations. As other causes of mortality and morbidity have been eliminated or reduced, malformations have become increasingly prominent. Although there is not universal agreement, the great majority of investigators find a two-to threefold increase in malformations in infants of insulin-dependent diabetic mothers. This increase is not seen in infants of gestational diabetics. It probably is not present in women whose diabetes can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
200
1
10

Year Published

1986
1986
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(218 citation statements)
references
References 28 publications
7
200
1
10
Order By: Relevance
“…Although a planned pregnancy with optimal blood glucose control and folic acid supplements at the time of conception reduces the risk of congenital malformations, a recent prospective study showed that the incidence of congenital malformations is still elevated in women with type 1 diabetes [4]. The congenital malformations associated with diabetic pregnancy affect many major organs, including the central nervous, cardiovascular, gastrointestinal, urogenital and musculoskeletal systems [5,6]. The pathogenesis of congenital anomalies is complex and still poorly understood, although it has been suggested that excessive reactive oxygen species (ROS) associated with hyperglycaemia are responsible for the increased risk of malformation [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Although a planned pregnancy with optimal blood glucose control and folic acid supplements at the time of conception reduces the risk of congenital malformations, a recent prospective study showed that the incidence of congenital malformations is still elevated in women with type 1 diabetes [4]. The congenital malformations associated with diabetic pregnancy affect many major organs, including the central nervous, cardiovascular, gastrointestinal, urogenital and musculoskeletal systems [5,6]. The pathogenesis of congenital anomalies is complex and still poorly understood, although it has been suggested that excessive reactive oxygen species (ROS) associated with hyperglycaemia are responsible for the increased risk of malformation [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…For a diabetic woman the risk of bearing a malformed child is 2-3 times higher than for a normal woman [1], and compared with normal pregnancies a greater proportion of the congenital malformations in diabetic pregnancies are lethal [2][3][4]. The exact pathogenesis of the malformations is at present unknown.…”
mentioning
confidence: 99%
“…Congenital defects typical for diabetes, such as caudal regression syndrome or central nervous system, often are due to hyperglycemia before pregnancy especially among obese women and not detected type 2 diabetes [18]. Many studies demonstrate the importance of pregnancy planning in women with pregestational diabetes, but also among women with other metabolic disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies demonstrate the importance of pregnancy planning in women with pregestational diabetes, but also among women with other metabolic disturbances. It turned out that both normalization of glucose levels during pregnancy and neonatal outcomes were better in women who planned their pregnancy [18,19]. Maintaining normal glycemia, especially in the first trimester, is essential for preventing congenital defects [18].…”
Section: Discussionmentioning
confidence: 99%